Partisipasi Masyarakat dalam Pengelolaan Dana Desa (Studi Kasus di Desa Karangtengah, Kecamatan Baturraden, Kabupaten Banyumas) - Farrah Eva Nabila; Alizar Isna; Sukarso Sukarso (Universitas Sultan Ageng Tirtayasa, 2023)
Each village initiated various efforts on behalf of the community empowerment program funded through the village fund, such as in Karangtengah Village, Baturraden Subdistrict, Banyumas Regency. The purpose of this research is to know the participation and decentralization in community empowerment program through village fund in Karangtengah Village, Baturraden Subdistrict, Banyumas Regency. The research method used in this study is a qualitative method. Selection of informants using purposive sampling technique selection of informants who really understand about the information object research and informants can be trusted as a source of data competent and to obtain data. Data collection is used with in-depth interviews, observation and documentation. Data analysis method used is interactive analysis method. The results showed that participation in planning, implementing, controlling and utilizing the results of community empowerment programs through village funds in 2016 was still considered to be less active. Many Karangtengah villagers have not received and utilized the results of the program. Similarly, decentralization carried out in planning, implementing, controlling, and utilizing the results of the community empowerment program through village funds in 2016 is considered to be still top down or only through program managers, be it village officials, sub-district commands, or district commands. So, some community empowerment programs in Karangtengah Village are not based on the needs of the Karangtengah Village community. For this reason, several community empowerment programs in Karangtengah Village perspective that have been studied, not yet able to empower the community.